English Program Students’ Perceptions of Instagram Reels for Vocabulary Acquisition - Adid, Al Mujaddid; Mahdum; H. M. Syarfi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study investigates English Study Program students’ perceptions of Instagram Reels as a tool for vocabulary acquisition at FKIP Universitas Riau. A quantitative descriptive design was employed. Data were collected using a 30-item closed-ended questionnaire adapted from the Technology Acceptance Model (TAM) and Mobile-Assisted Language Learning (MALL) frameworks. The population comprised 113 students from the 2024 cohort, and 88 students were selected through purposive sampling using the Slovin formula. The results indicate positive perceptions of Instagram Reels for learning new vocabulary, with an overall mean score of 3.83 (High). Across six indicators, students reported generally high perceptions, with the highest mean in Access to Mobile Devices (M = 4.06: Very High) and the lowest mean in Learning Resources (M = 3.67: High). Overall, Instagram Reels is perceived as an accessible and useful medium to support vocabulary learning among the participants.